Guaranteed predictive estimation of solutions of system of differential equations with the Gompertzian dynamics - Наконечний, О.; Зінько, П.; Шевчук, Ю.; Nakonechnyi, O.; Zinko, P.; Shevchuk, I. (Lviv Politechnic Publishing House, 2019)
У роботі досліджено математичну модель у формі системи нелінійних диференціальних рівнянь із динамікою Гомперца, яка може бути застосована для моделювання процесів, що швидко зростають за часом. Сформульовано та розв’язано задачу знаходження гарантованих прогнозних оцінок для систем диференціальних рівнянь з динамікою Гомперца для випадку неперервних спостережень. Як приклади подано результати визначення гарантованих прогнозних оцінок динаміки математичної моделі поширення одного виду інформації в соціумі.

In this paper, we have introduced a mathematical model to describe processes that grow in time rapidly. The model has the form of a system of non-linear differential equations with Gompertzian dynamics and non-stationary parameters. We have formulated and studied the problem of finding the predictive estimation for the systems of differential equations with Gompertzian dynamics, for the case of continuous observation. We have suggested the algorithms for building guaranteed predictive estimations for the model. We have presented as an example, the results of numerical experiments to build guaranteed estimates for the mathematical model of spreading some type of information in society. The suggested approach presents both theoretical interest and important practical meaning.
Гарантовані прогнозні оцінки розв‘язків систем диференціальних рівнянь із динамікою Гомперца
Keywords: системи нелінійних диференціальних рівнянь; динаміка Гомперца; прогнозні гарантовані оцінки; невизначеність; system of differential non-linear equations; Gompertzian dynamics; guaranteed predictive estimation; uncertainty; 517.9; 519.87